Lectinology 4.0: altering modular (ga)lectin display for functional analysis and biomedical applications - Ludwig, Anna-Kristin; Kaltner, Herbert; Kopitz, Jürgen; Gabius, Hans-Joachim (Biochimica et biophysica acta. Specialized section on biophysical subjects, 2019)
BACKGROUND: Recognition of glycans by lectins is emerging as (patho)physiologically broadly used mode of cellular information transfer. Whereas the direct ligand-receptor contact is often already thoroughly characterized, the functional relevance of aspects of architecture such as modular design and valence of lectins is less well defined. - SCOPE OF REVIEW: Following an introduction to modular lectin design, three levels of methodology are then reviewed that delineate lectin structure-activity relationships beyond glycan binding, with emphasis on domain shuffling. - MAJOR CONCLUSIONS: Engineering of variants by modular transplantation facilitates versatile Nature-inspired design switches and access to new combinations with translational potential, as exemplified for human adhesion/growth-regulatory galectins. - GENERAL SIGNIFICANCE: To gain an understanding of the functional significance of natural variations in quaternary structure and modular design within a protein family is a current challenge. Strategic application of methods of the described phases is a means to respond to this challenge.
Gesehen am 09.09.2019